ChemInform Abstract: Design and Synthesis of Phosphite Ligands for Homogeneous Catalysis. Issue 17 (4th April 2013) - Gual, Aitor; Godard, Cyril; de la Fuente, Veronica; Castillon, Sergio
Abstract Review: 316 refs.